In planta transformation methods to accelerate the domestication of perennial grain crops - Correia, Pedro M. P.; Dong, Xinyi; Chen, Mengming; Nørrevang, Anton Frisgaard; Luo, Guangbin; Palmgren, Michael (Frontiers in Plant Science, 2025)
The domestication of grasses has historically favored annual species due to their rapid growth and suitability for crop rotation; however, such crops rely heavily on human input. In contrast, perennial grasses, which live for multiple years, offer significant environmental benefits, such as improved soil health and natural resilience to biotic and abiotic stress, but have not yet been domesticated. Gene editing of yield-related genes presents an opportunity to improve yield stability in perennial cereal crops. However, this process typically requires transformation to introduce gene-editing tools, and many perennial grasses are recalcitrant to traditional in vitro transformation. Alternative in planta transformation methods have recently emerged, offering simpler, faster, and more genotype-independent approaches. These methods bypass the need for tissue culture and could potentially be used to transform recalcitrant plants more efficiently. In this review, we evaluate the potential of in planta transformation methods for developing perennial cereal crops and advocate for exploring the role of such crops in sustainable agriculture.